2021
DOI: 10.1097/ncc.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Smart Pill Bottle Reminder Intervention on Medication Adherence, Self-efficacy, and Depression in Breast Cancer Survivors

Abstract: Background: Globally, breast cancer has been identified as the most common cancer among women. The clinical efficacy of adjuvant oral antiestrogen therapy-including tamoxifen and aromatase inhibitors-has been proven to be clinically efficacious for breast cancer survivors. However, medication adherence for these therapies remains suboptimal among breast cancer survivors. Objective: The aim of this study was to evaluate the effect of a reminder intervention-a smart pill bottle paired with the Pillsy mobile appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…A total of 13% (4/30) of the studies [ 32 , 37 , 44 , 45 ] reported self-efficacy as an outcome. Pooling of studies showed a statistically significant effect size favoring the intervention group (SMD=0.15, 95% CI 0.02-0.29; P =.03; I 2 =28%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13% (4/30) of the studies [ 32 , 37 , 44 , 45 ] reported self-efficacy as an outcome. Pooling of studies showed a statistically significant effect size favoring the intervention group (SMD=0.15, 95% CI 0.02-0.29; P =.03; I 2 =28%).…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis for depression included 1511 patients from 43% (13/30) of the studies [16,[18][19][20]25,28,30,32,33,[35][36][37]45]. A random-effects model was chosen for analysis owing to the significant heterogeneity among the 43% (13/30) of the studies (P<.001; I 2 =81%).…”
Section: Effects On Depressionmentioning
confidence: 99%
“…Previous studies showed that the use of new technologies such as mobile applications as one of the influential factors in promoting medication self‐efficacy. 43 , 44 Achieving the same results, despite the use of different tools as well as variety of interventions and methods of using the smartphone capabilities, can be attributed to the fact that the information technology and internet advances as well as numerous advantages such as easy access, availability at any time and place, communication and information transfer capability, 45 facilitate the learning process, and improve the information satisfaction, as one of the factors affecting patient satisfaction is the teaching method. 46 Thus, as learning enhances, patients receive more information about their disease and can participate effectively in their treatment course.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Park et al's 42 also supported the effectiveness of mobile‐based education in promoting adherence to antiplatelet drug therapy during the 30 days of vulnerability after myocardial infarction or percutaneous coronary interventions. Previous studies showed that the use of new technologies such as mobile applications as one of the influential factors in promoting medication self‐efficacy 43,44 . Achieving the same results, despite the use of different tools as well as variety of interventions and methods of using the smartphone capabilities, can be attributed to the fact that the information technology and internet advances as well as numerous advantages such as easy access, availability at any time and place, communication and information transfer capability, 45 facilitate the learning process, and improve the information satisfaction, as one of the factors affecting patient satisfaction is the teaching method 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Pillsy, which has successfully and significantly increased adherence in other treatment areas, acts like a digital medication coach, providing reminders using a mobile app, text messages, and automated phone calls [ 22 ]. The platform automatically tracks doses and timing and sends intelligent reminders to create a unique feedback loop, which allows the developers to constantly optimize incentive or reminder messages to meet user needs and increase adherence.…”
Section: Introductionmentioning
confidence: 99%